Early Childhood Physical Motor Development - Al Ihzan Tajuddin; Ronald Dwi Ardian Fufu; Salmon Runesi (Universitas Nusa Cendana, 2022)
Motor development is one aspect that must be considered in its development in early childhood. Motor development is often used as a benchmark to prove that children are growing and developing well. Motor development is something that talks about coordinated physical movements, so that in its development it takes a variety of appropriate stimulation for early childhood. Motor development is one of the most important factors in the development of the individual as a whole. Basically, this development develops in line with the maturity of the nerves and muscles of the child. Thus, every movement, no matter how simple, is the result of a complex interaction pattern of various parts of the system in the body that is controlled by the brain. The results of this study indicate that children who have good physical-motor development, when children are able to coordinate their body muscle movements optimally. Conducive environment, parenting patterns, nutritious food are factors that support children's physical-motor development, especially when they are still under the age of five (toddlers).